A randomized, controlled trial to investigate cognitive behavioral therapy in prevention and treatment of acute oral mucositis in patients with locoregional advanced nasopharyngeal carcinoma undergoing chemoradiotherapy - He, Li-li; Xiao, Shuai; Jiang, Cui-hong; Wu, Xiang-wei; Liu, Wen; Fan, Chang-gen; Ye, Xu; Zhao, Qi; Wu, Wen-qiong; Li, Yan-xian; Wang, Hui; Liu, Feng (Frontiers in Oncology, 2023)
Purpose Oral mucositis is a common side effect of concurrent chemoradiotherapy (CCRT). This study aimed to determine whether cognitive behavioral therapy (CBT) could help prevent oral mucositis during chemoradiation therapy for locoregional advanced nasopharyngeal carcinoma (LA-NPC). Methods and materials Between July 15, 2020, and January 31, 2022, a randomized controlled phase II trial was conducted. Eligible patients (N=282, 18-70 years old) with pathologically diagnosed LA-NPC were randomly assigned to receive CBT or treatment as usual (TAU) during CCRT (computer-block randomization, 1:1). The primary endpoints were the incidence and latency of oral mucositis. Results The incidence of oral mucositis was significantly lower in the CBT group (84.8%; 95% confidence interval [CI], 78.7%-90.9%) than in the TAU group (98.6%; 95% CI, 96.6%-100%; P<0.001). The median latency period was 26 days and 15 days in the CBT and TAU groups, respectively (hazard ratio, 0.16; 95% CI, 0.12-0.22; P<0.001). CBT significantly reduced ≥ grade 3 oral mucositis (71.9% vs. 22.5%, P<0.001), dry mouth (10.8% vs. 3.7%, P=0.021), dysphagia (18% vs. 5.1%, P=0.001), and oral pain (10% vs. 3.6%, P=0.034) compared with TAU. Patients receiving CBT and TAU during CCRT had similar short-term response rates. Conclusions CBT reduced the occurrence, latency, and severity of oral mucositis in patients with LA-NPC during CCRT.